Diagnóstico das condições de vida e trabalho dos mototaxistas cooperados: um estudo na Cooperativa Mista dos Mototaxistas de Parintins (COOPMOTO) - Alfaia, Lucas dos Passos (Brasil, 2024)
The research addressed the professional life of motorcycle taxi drivers, a category that plays a fundamental role in the transport sector of the Brazilian economy, operating in different regions of the country as an alternative to obtaining a source of income. The central problem of the research was to identify the main difficulties faced by motorcycle taxi drivers in Parintins when carrying out their professional activities, and how these challenges affect their working conditions and quality of life. In summary, the general objective of the study was to diagnose the living and working conditions of motorcycle taxi drivers in the municipality of Parintins. Additionally, specific objectives were defined: to survey the socioeconomic profile of motorcycle taxi drivers; verify the changes in the lives of motorcycle taxi drivers after entering the activity; and understand the difficulties involved in exercising the profession of motorcycle taxi drivers. It consisted of qualitative research, and field research was adopted as a methodology. To construct the data, the open question questionnaire and bibliographic review were used as research techniques, reviewing relevant sources for the context of the topic, based mainly on theorists Rios (2006) and Teixeira et al. (2017). The justification for the research lies in the pressing need to understand the reality of these professionals, a group that is often unprotected, and the importance of promoting a safer and more equitable work environment at a national level. Finally, the results obtained from the content analysis technique indicate a need for public policies for better living conditions, mainly due to the lack of social security benefits, exposure to occupational risks and income instability, seeking solutions to promote well-being, combining the regulation of the profession, inspections and provision of rights, as these professionals play a fundamental role in urban mobility and the economy of many municipalities in the country.